ICNP® and Healthcare Reform — readiness for engagement - Hussey, Pamela; Adams, Elizabeth; Matthews, Anne (Nursing Problems / Problemy Pielęgniarstwa, 2017)
Nursing and Midwifery involvement in advancing the eHealth agenda is variable across member states within the European Union. Across the European Union, citizens are increasingly considered as consumers of health care with the reorientation of health care services to be less rigid, more flexible and service orientated. There is a growing realisation that technology adoption relating to health and social care is increasingly viewed as a complex process and requires focused attention. The aim of the study is to show that the profession of nursing and midwifery has in deployment of technology within health and social care. A core requirement of integrated care is the need for an agreed standardised language to facilitate shared electronic health records.